Comportamento em fadiga e corrosão fadiga da liga Ti6A14V oxidada termicamente - Santos, Silvando Vieira dos (2014)
Fatigue and fracture assisted by the environment are responsible for the majority of failures in implants. Due to low tribological properties of titanium alloys, the thermal oxidation technique has been evaluated to improve the surface hardness and consequently, to improves the tribological properties of Ti6Al4V alloy. However, despite improved tribological properties of the Ti6Al4V alloy, there is a tendency to reduction of the fatigue limit of the oxide layer. The combined action of body fluid and cyclic loads also need to be investigated. This study evaluated the effect of thermal oxidation in the fatigue limit of the Ti6Al4V in environment containing 0.9% NaCl. It was observed a reduction in the fatigue limit for thermally oxidized Ti6Al4V alloy and it is suggested that the reduction in fatigue properties of alloy is associated with the brittleness of oxide layer.